P365Does papillary muscle ablation affect mitral valve function: a single centre experience. (18th June 2020) - Stassen, J; Dilling, D; Vijgen, J; Schurmans, J; Koopman, P
Abstract: Introduction: Ventricular arrhythmias from papillary muscles (PMs) often require extensive catheter ablation (CA). Not much is known about the mitral valve (MV) function after these extensive catheter ablations. Purpose: The goal of this study was to determine the impact of papillary muscle CA on MV function. Methods: We retrospectively examined echocardiographic measurements in 21 patients with frequent premature ventricular contractions (PVCs) originating from the mitral PMs who underwent CA, dating from October 2012 till November 2018. We assessed MV function at baseline, 6 month and last follow-up. Degree of mitral regurgitation (MR) was graded as mild (ERO <0, 2 cm2, regurgitation volume (RV) <30ml), moderate (ERO 0, 2-0, 4cm2, RV 30-59ml) or severe (ERO ≥0, 4cm2, RV ≥60ml). Significant MR was defined as a 2+ change. Results: Mean age of the study population was 59, 7 (27-80)years, 52, 4% was female. 2 patients were known with ischemic heart disease. There was a family history of sudden cardiac death in 3 patients. Main symptoms at presentation were palpitations (66, 7%), fatigue (33, 3%), dyspnea (33, 3%, all NYHA 2), dizziness (28, 6%), angina pectoris (14, 3%) and syncope (4, 8%). Beta blocker (71, 4%), flecaïnide (23, 8%), amiodarone (9, 5%), sotalol (4, 8%) and propafenon (4, 8%) were the most frequent medical therapies before CA. Mean burden of PVC before ablation was 15 574 (2000-39700)/24h. In 28, 6% non sustained VT was documented, 1 patient suffered a sustained episode of VT. After ablation, mean burden of PVC was reduced to 1331 (0-14200)/24h. Redo ablation was necessary in 28, 6% of patients. PVCs orginated from the anterolateral PM in 33, 3% and from the posteromedial PM in 66, 7%. Mean troponin release was 9.4 ± 5.3 µg/l, mean troponin hs (since 2016) was 1591.0 ±658.6ng/ml. CMR was done in 14/21 (66, 7%) patients before CA. In 5 out of 14 patients (35, 7%), delayed enhancement at the papillary muscles was noticed. In 5 patients without delayed enhancement, CMR was repeated after CA. In all these 5 patients, delayed enhancement was noticed at the level of the papillary muscles. At baseline, 15/21 had mild, 5/21 moderate and 1/21 severe MR. There was no significant chance in MR at 6m follow-up with 15/21 having mild and 6/21 moderate MR (p 0.58) with 1 patient having a significant MR 2+ change. At last follow-up (23.7 ± 22.6 months) there was also no significant chance in MR with 15/21 having mild and 6/21 moderate MR (p 0.58) without a significant MR 2+ change. Complications occurred in 1 patient (transient AV blok). No patients died during follow up. Conclusions: Although PM ablation was associated with time extensive ablation, significant troponine release and documented delayed enhancement on post ablation MRI, there was no risk of additional valvular dysfunction after CA in this study. Larger studies will be necessary to confirm these findings.